Severe Haemolytic Anaemia, a Rare Presentation of Nutritional Vitamin B12 Deficiency: A Case Report (Nepalese Medical Journal, 2019)
Vitamin B12 deficiency usually presents with megaloblastic anemia, pancytopenia, and neurological symptoms. The cause is usually, nutritional deficiency, increase demand, decrease absorption. This report describes a case with symptoms of apathy and findings suggestive of severe hemolytic anemia, diagnosed with vitamin B12 deficiency. Haemolysis is a rare hematological finding in cases of B12 deficiency, and descriptions of a nutritional vitamin B12 deficiency, without evidence of pernicious anaemia, causing haemolysis, are even scarcer, and this paper was intended to draw physicians’ attention to this rare form of presentation.